Analisis Faktor-Faktor yang Memengaruhi Pendapatan Sektor Pariwisata Sebelum dan Saat COVID-19 di Jawa Tengah - Qothrunnada, Farah Yuli; Anwar, Nurul; Alfarisy, Muhammad Farid (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
The COVID-19 pandemic has greatly affected the economy in Indonesia, especially in the tourism sector in Central Java. The development process of an area or region is supported by tourism industry activities that can increase community and regional income. The purpose of this study is to analyze the influence of the number of visitors, accommodation, GRDP (Gross Regional Domestic Product) per capita, infrastructure, tourist growth before and during the COVID-19 pandemic. This research method is purposive sampling. Purposive sampling is a data retrieval technique based on certain considerations. This study used secondary data obtained from BPS (Central Statistics Agency) and Disporapar (Youth, Sports and Tourism Office) of Central Java Province. The results of this study show that the variable number of visitors has a positive and significant effect on the income of the tourism sector in Central Java, the accommodation variable has a positive and significant effect on the income of the tourism sector in Central Java, the variable GRDP per capita has no effect on the income of the tourism sector in Central Java, the variable of tourism infrastructure does not affect the income of the tourism sector in Central Java, and the variable of tourist growth significant positive effect on tourism sector income in Central Java. The implication of this research is to maintain economic stability, especially the tourism sector, so as not to decrease income when a pandemic occurs. Tourism business actors and the government are expected to advance tourism such as, developing tourist attractions, adding attractive accommodations so that tourists outside the region are interested in visiting so that government income in the tourism sector increases.